Mediação pedagógica e Sequência Fedathi: contributos para o desenvolvimento do raciocínio lógico-matemático de crianças e adolescentes com mielomeningocele no contexto hospitalar de reabilitação em Fortaleza/Ceará/Brasil - Oliveira, Silvia Sales de (2022)
The inclusion of students with disabilities in regular education has caused educational demands and pedagogical monitoring in hospital rehabilitation environments. In this perspective of inclusive education are children with Myelomeningocele (MMC), who have congenital alterations in the closing of the neural tube and may have intellectual deficiencies that affect the development of logical-mathematical reasoning and the learning of school contents, such as mathematics. This research aimed to analyze the contributions of pedagogical mediation in the context of rehabilitation, based on the Fedathi Sequence, to stimulate the development of logical-mathematical reasoning in children and adolescents with Myelomeningocele, aged between 9 and 13 years. The theoretical framework was supported by authors such as Borges Neto and Dias (1991); Towers (2017); Souza (2013); Mazzota (2005); Camargo, Gomes and Silveira (2016); Braga (1995 and 2008); Braga and Paz Junior (2000); Matos, Mugiatti (2014); Piaget (1967, 1971 and 2009); Vygotsky (1978, 1987, 1994); Feuerstein (1986, 1997 and 2012), among others, to support the research. The methodological course of this research was characterized by an investigation with a qualitative approach, which was configured in an action research using participant observation and obtaining data through semi-structured interviews with those responsible for the study participants, documental research in medical records Patient Electronics and the characterization of the logical-mathematical reasoning of children and adolescents with the diagnosis of Myelomeningocele, subjects of the study, through pedagogical assessment. From this characterization it was possible to outline a proposal for pedagogical mediation in a hospital context of rehabilitation based on the contributions of the Fedathi Sequence. The field research was carried out in the Child Rehabilitation Program of the Neurorehabilitation Center – SARAH, Fortaleza unit. The data from the participant observations in the moments of pedagogical mediations and the participants' speech were recorded in audio, categorized and analyzed based on the theory of Content Analysis by Bardin (2011). It was found that pedagogical mediation in the context of rehabilitation, based on the principles of the Fedathi Sequence, enabled greater participation and engagement of children and adolescents in stimulation activities, provided the organization of cognitive facilitators and the promotion of situations to assist in the development of the logical-mathematical reasoning, in addition to the greater understanding of family members about the challenges of learning mathematical content at school due to the diagnosis of Myelomeningocele. It is concluded the importance of pedagogical mediation in the development of children and adolescents with disabilities in the context of rehabilitation and the relevance of a reflexive teaching action, supported by the Fedathi Sequence, for the adoption of pedagogical strategies that give children and adolescents with disabilities the opportunity to learning situations that can leverage development, making them participatory and active in knowledge construction processes and in their rehabilitation.